Winning Conditions of Precarious Workers’ Struggles: A Reflection Based on Case Studies from South Korea - Lee, Byoung-Hoon; Lee, Sophia (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2017)
In South Korea, many struggles of non-regular workers, who attempted to organize their unions and engage in militant action to protest against employers’ inhumane discrimination and illegal exclusion, have failed to achieve the desired outcomes, due to their vulnerable employment status and their lack of action resources. In this light, our study examines the conditions that lead to victory in precarious workers’ struggles, by focusing on three attributes: internal solidarity with regular workers, external solidarity from labour and civil society groups outside the workplace, and mobilized protest repertoires. Specifically, this study seeks to identify the configurations of these three conditions that produce successful outcomes in precarious workers’ struggles, in terms of bargaining gains and organizational sustainability. We do this by employing fs/QCA modelling to examine 30 major cases of non-regular worker struggles occurring over a 16-year period from 1998 to 2013.Our analysis presents the finding that the conditional configuration of strong external solidarity, strong internal solidarity, and fewer struggle repertoires constitutes a significant causal path to successful outcomes. This reaffirms the idea that strong solidarity bridging, whether with regular workers that have a different employment status in the segmented workplace, or with labour and civil society groups outside the workplace, is the crucial causal condition for precarious workers to achieve their desired outcomes from struggle. An unexpected finding, however, is that when precarious worker struggles mobilize fewer struggle repertoires, they are likely to achieve the successful outcomes of bargaining and organizational gains. Our study contributes to the theoretical elaboration of labour movement revitalization for the precariat class, by shedding light on the activism of precarious workers, considering that the English-language literature that pays attention to the active role of such atypical workers in staging protests against employers’ inhumane treatments and the neoliberal labour regime is limited.